Centro de interés chicas stem, experiencia innovadora En el colegio Heladia Mejía IED (Memorias Sifored - Encuentros Educación UAN, 2023)
Among the different goals proposed worldwide to reduce the gender gap, the 2030 Agenda for Sustainable Development is formulated, which includes 17 Sustainable Development Goals (SDGs), of which SDGs 4 and 5 focus on quality education and gender equality respectively. From this foundation, as well as from the current and future relevance of increasing the participation of women in the field of science and technology, an interest center is created at the Heladia Mejia IED School, which was founded with the objective of presenting STEM areas as an opportunity to strengthen gender equality. The STEM Girls interest center of the Heladia Mejia School IED, generates in the students an alternative motivation and interest to their daily school environment, allowing them to spend their free time in activities that strengthen their knowledge and skills, particularly in the STEM areas.
Keywords: inclusion; innovation; STEM; girls; gender